GAME THEORY ANALYSIS OF PROSPECTS OF FORMAL AND INFORMAL INSTITUTIONS TOBACCO INDUSTRY IN GRESIK REGENCY - Gigih Pratomo; Adhitya Wardhono; Ciplis Gemah Qo’riah; Satrio Wicaksono (UNEJ e-Proceeding, 2012)
Institution is a rule of the game and organizations that play an important role in regulating the use and allocation of resources in an efficient, equitable and sustainable [1][2][3][9]. Institution will provide an important change in terms of industrial and agricultural sectors in tobacco plants. The research aims to identify prospects existence of formal and informal institutions against the tobacco industry in Gresik. The research data isprimary and secondary data. Research sites focused on Gresik. Technical analysis of data is using descriptive analysis and game theory. The results showed that the existence and role of formal and informal institutions will provide a new euphoria in the tobacco industry in Gresik. This is indicated by an effort to increase awareness of the importance of communication between economic actors in the tobacco industry.